Análise experimental de técnicas de modulação E-OFDM na comunicação via luz visível - Monteiro, Felipe Teixeira (2019)
A performance comparison between a multicarrier modulation scheme candidate of 5th generation mobile phone (5G) applied to Visible Light Communications (VLC) is presented in this work. The VLC technology is considered promising to due the advantages of including the use of Light-Emitting Diode (LED) for unlicensed spectrum data transmission, and the absence of electromagnetic interference with wireless communication conventional systems. Its integration of VLC technology in the 5G context presupposes a performance assessment among the recommended 5G modulation techniques, as well as comparison with the modulation assigned to fourth generation mobile telephony (4G). Therefore, the performance of VLC systems with Orthogonal Frequency Division Multiplexing (OFDM), modulation used in 4G systems, is compared with two new modulation scheme candidate for 5G standardization, which is Filter Bank Multiarrier (FBMC) and the generalized version of unorthogonal subcarrier multiplexing (GFDM - Generalized Frequency Division Multiplexing). Results obtained after the numerical simulations in channels that add white Gaussian noise showed that FBMC modulation technique achieves better performance when compared to OFDM and GFDM multiplexing. The experimental setup of a VLC channel with transmitter LED and photoreceiver was prepared and explored to prove the principles discussed. Experimental results showed that for a VLC link of 1 m length and for different values of the Signal-to-Noise Ratio (SNR), the GFDM scheme presented better performance when compared to OFDM, although for SNR ≤ 8 dB values FBMC had better performance among the others. This is also true when the link length reaches values ≈ 2.5 m for high SNR values. However, to the ≈ 5 dB gain in the magnitude metric of the error vector obtained at d = 2.5 m reinforces the idea that both FBMC and GFDM can be adopted for VLC communication in Indoor environments, used as a complementary system of 5G applications. Nevertheless, we conjecture that for link lengths d > 2.5 m, FBMC can be the favorite modulation scheme, regarding the rapid performance degradation of GFDM based VLC systems